The role of salience in performance schemes: Evidence from a field experiment - Florian Englmaier; Andreas Roider; Uwe Sunde (Center for Economic Studies and ifo Institute (CESifo), 2012)
Incentive schemes affect performance and priorities of agents but, in reality, they can be complicated even for simple tasks. We analyze the effects of the salience of incentives in a team production setting where the principal has an interest in quantity and quality of output. We use data from a controlled field experiment that changed the communication of the incentive system without changing the incentive system. The results indicate that salience of incentives itself is statistically and economically important for performance. We find that higher salience of incentives for quantity increases quantity, reduces quality, and increases in-pocket income of team managers.
Keywords: M52; J30; D03; D80; 330; incentives; attention; salience; communication; field experiments; Leistungsanreiz; Kommunikation; Arbeitsgruppe; Arbeitsleistung; Prinzipal-Agent-Theorie; Feldforschung